ALASAN MENDESAK SEBAGAI SYARAT DISPENSASI NIKAH DALAM UU NO. 16 TAHUN 2019: (Analisis Yuridis Terhadap Putusan Pengadilan Agama Sentani No.16/Pdt.P/2021/PA.Stn) - Suherman, Heru Andryana; Marwah, Marwah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The institution of marriage plays a significant role in the human experience. Law No. 16 of 2019 lays forth the general principles that will govern marriage law. Religious courts have the authority to waive or reduce the minimum age limit for marriage for those who are less than 19 years old for males and 16 years old for women. For the purpose of this study, we use a normative juridical method to investigate questions about the relationship between statutory and regulatory frameworks. Notwithstanding this, the courts often make exceptions when it comes to weddings. There is a critical need, as well as strong evidence, to redouble our efforts to limit the number of marriages that take place between children.